P-EUS01 Pancreatic metastases from Renal Cell Cancer; endosonographic features and outcomes of a rare clinical entity. (16th December 2021) - Ahmed, Wafaa; Farman, Muhammad; Joshi, Deepak; Harrison, Phillip; Devlin, John; Reffitt, David
Abstract: Background: The pancreas is a rare site for metastatic deposits in the absence of disseminated metastatic disease. They can be difficult to differentiate from primary pancreatic malignancy based on the clinical history and radiological features alone. Renal cell cancer (RCC) is the most common source. We describe their endosonographic characteristics and clinical outcomes. Methods: Patients undergoing EUS- FNB with a positive diagnosis of pancreatic metastatic disease from RCC from 2017 to 2019 were retrospectively identified. Recorded variables included patient demographics, endosonographic features and patient outcomes. Results: Five patients were identified. Mean age was 63 (range 53-72 years old). Mean time from diagnosis of the primary RCC to diagnosis of pancreatic metastasis was 12.75 years (range 6-18 years). All had resection of the primary lesion. Mean diameter on EUS was 37.80mm (range 15mm to 100mm). The lesions were homogenous, well-circumscribed, hypoechoic and hypervascular. Tissue acquisition was performed using a 22G FNB needle. Two underwent surgical resection of the metastasis, one of which had recurrence at the surgical bed after 26 months. One had disseminated malignancy at the time of diagnosis. One passed away prior to surgical resection. Conclusions: Pancreatic metastasis from renal cell cancer have characteristic endosonographic features and can present many years after initial diagnosis and resection. EUS-FNB has a central role in confirming this diagnosis.